Little & Lion - Colbert, Brandy (Little, Brown and Company, 2018)
Suzette returns home to Los Angeles from boarding school and grapples with her bisexual identity when she and her stepbrother Lionel fall in love with the same girl. As Lionel's bipolar disorder begins to spin out of control, it forces Suzette to confront her own demons. Can she save Lionel from himself-- and will he trust her enough to do so?